2017
DOI: 10.18632/oncotarget.16666
|View full text |Cite
|
Sign up to set email alerts
|

The mutation of Trp64Arg in β3-adrenoreceptor-encoding gene is significantly associated with increased hypertension risk and elevated blood pressure: a meta-analysis

Abstract: This meta-analysis was implemented to test the association of a missense mutation, Trp64Arg, in β3-adrenoreceptor-encoding gene (ADRB3) with both hypertension risk and blood pressure (BP) changes. A systematic search of three publicly-available databases was launched to look for articles published as of December 2016. Qualification appraisal and data extraction were independently done by two researchers. Pooled estimates were expressed as odds ratio (OR) or weighted mean difference (WMD), and their 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
2
0
0
1
Order By: Relevance
“…This study also showed that the co-association of FAM13A rs1903003 (CC) and the β3-AR Trp64 variant is related to higher blood pressure values (SBP and DBP). Thus, these data correspond with other studies which have proved that the Trp64Arg polymorphism of the β3-AR gene is associated with increased metabolic disorders (diabetes mellitus) and hypertension risk [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study also showed that the co-association of FAM13A rs1903003 (CC) and the β3-AR Trp64 variant is related to higher blood pressure values (SBP and DBP). Thus, these data correspond with other studies which have proved that the Trp64Arg polymorphism of the β3-AR gene is associated with increased metabolic disorders (diabetes mellitus) and hypertension risk [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…The familial history of comorbidities related to cardiometabolic traits (diabetes, hypertension, dyslipidemia and obesity) was not significantly associated with GIPR Glu354Gln genetic polymorphism. Hypertension associated factors were male sex, advanced age, high BMI and smoking, corroborating literature data (18, 19, 20). The mechanisms involved in the pathophysiology of hypertension arise from the interaction among environmental and genetic factors.…”
Section: Discussionsupporting
confidence: 90%
“…또한 CAMK4, ADRB3 그리고 CYP11B2 유전자와 같이 고 혈압에 영향을 미치는 유전적 요인에 대한 연구도 활발 하게 진행되고 있다 (Li and Liu, 2014;Chen et al, 2016;Yang et al, 2017 (Zotova et al, 2016). 특히 안지오텐신 II 유형1 수용체(Angiotensin II type 1 receptor, AT1R)을 생성하는 ATR1(또는 AGRT1) 유전자의 유전적 다형성은 메타 분석을 통하여 아시아인 과 백인에서 고혈압 발병 위험과 관련이 있음이 확인되 었다 (Liu et al, 2015).…”
unclassified